Managing the Quality of Islamic Education in the Digital Era: Challenges and Strategic Framework in Batubara Regency, Indonesia - Irma Suryani; Mulkan Darajat Silaen; Muhammad Tafsir Tambunan (Bulletin of Indonesian Islamic Studies, 2025)
Islamic education in Batubara Regency faces major challenges in integrating digital technology into the learning process, which impacts the quality of management and educational outcomes in the era of the industrial revolution 4.0. This article aims to describe research findings on quality management in Islamic education, with a focus on the impact of technological advancements and strategies that can be employed to address them. The research employs qualitative methods, elucidating findings through interviews and observations, and analyzing data to gain profound insights into the management of Islamic education in maintaining quality in the digital era. The research findings reveal that quality management in Islamic education commences with a transformation in teaching methods, integrating technological access while upholding religious principles and the development of virtuous individuals. It also involves the effective management of human resources to ensure the advancement and future of Islamic education, conscientious financial management of madrasah education, recognizing the enduring connection of Islamic principles to all financial activities within education, and the continuous improvement of facilities and resources that support educational quality. Additionally, in managing conflicts within Islamic educational institutions, a rapid response to external input and the willingness to accept suggestions are vital in achieving educational excellence. The strategies implemented align with the requirements and needs of Islamic educational institutions. Furthermore, they must continuously enhance their technological capabilities and secure the necessary funding to meet the demands of Islamic education.